(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Law enforcement agencies in many countries have initiated the use of AFRS (Automated Facial Recognition System),it’s an artificial intelligence system that compares face traits automatically, to identify unknown suspects using images and other social media platforms. Its capabilities are fast developing in conjunction with artificial intelligence, and it has a lot of potential for solving crimes. However, it also has a negative connotation. There are substantial privacy and ethical considerations that necessitate legislation and regulation. The Ministry of Home Affairs of India has released a new plan for AFRS aimed at upgrading law-enforcement agencies for the purpose of detection of criminals, proper data exchange among law enforcement agencies throughout the globe. It is indeed evident to say, India is third largest country in technological development and the citizens are coping up with these changes. The author proposes to examine the emergence of Automated Facial Recognition System, contemporary uses, and legislative developments in various countries like US, UK and Australia, as well as doing an ethical examination of the concerns that may arise during its implementation. The author will also implicate the authenticity of FIR registered against unknown person through the use of AFRS, and legislations related to it. Ethical considerations are used to mediate conflicting issues with reference to modern innovation vis-à-vis public safety mechanism, privacy and democratic responsibility.